STRATEGI PEMASARAN JASA PENDIDIKAN DI MA PERGURUAN MUALIMAT CUKIR JOMBANG - Asy'ariy (Al Tadib : Jurnal Ilmu Pendidikan, 2022)
The article is intended to describe the marketing strategy of education in MAPM Cukir Jombang. The focus of the study is to find the pattern of MAPM strategy as an integral gender-based education institution with Islamic boarding school in marketing the existing education. With qualitative descriptive approach using observation data collection techniques, interviews, and documentation, the data were analyzed with three steps of data condensation, data display, and verification to draw conclusions. Result of research indicate there are 3 pattern of educational marketing strategy, first, strategy of strengthening education product which is done continuously as educational institution with special gender integrated with princess princess, second, alumni network strengthening strategy based on the idea that alumni as an integral part of the institution must become a major part in the development and strengthening of existence of the school, and third, analog and digital promotions, targeting all segments to keep the institution, excellence and product superior. Analog is conventional and digital through various ways with the utilization of information technology